CONTRIBUTION OF CREATIVITY TO MATHEMATICAL PROBLEM SOLVING SKILLS OF 5th GRADE STUDENTS PUBLIC ELEMENTARY SCHOOL OF IV NAGARI DISTRICT SIJUNJUNG REGENCY - Maifit Hendriani; Akmal Rijal (IAIN Ambon, 2020)
Abstract This study aims to describes the creativity and mathematical problem solving skills also the contribution of creativity to mathematical problem solving skills of 5th grade students public elementary school of IV Nagari District, Sijunjung Regency. Type of this study is correlational research. The population is 5th grade students all of IV Nagari District, Sijunjung Regency. The sampling technique uses is random sampling. The instrument for collects a data is a test of creativity and mathematical problem solving skills. The analysis technique uses is descriptive and correlational. The result shows: 1) 5th grade students public elementary school of IV Nagari District have high creativity as much as 18 students or 19.78%, high enough creativity as much as 31 students or 34.07%, high less creativity as much as 35 students or 38.46% and low creativity as much as 7 students or 7.69%. 2). High mathematical problem solving skills as much as 46 students or 50.55%, high enough mathematical problem solving skills as much as 13 students or 14.23%, high less mathematical problem solving skills as much as 21 students or 23.07% and low mathematical problem solving skills as much as 11 students or 12.08%. 3) There is a positive and significant contribution between creativity and mathematical problem solving skills with a correlation coefficient 0.426.